Dysregulated Host Response in Severe Acute Respiratory Syndrome Coronavirus 2-Induced Critical Illness. (18th January 2021) - Tiwari-Heckler, Shilpa; Rauber, Conrad; Longhi, Maria Serena; Zörnig, Inka; Schnitzler, Paul; Jäger, Dirk; Giese, Thomas; Merle, Uta
Abstract: Background: Impaired immune response has been reported to be the cause of the development of coronavirus disease 2019 (COVID-19)-related respiratory failure. Further studies are needed to understand the immunopathogenesis and to enable an improved stratification of patients who are at risk for critical illness. Methods: Thirty-two severely ill patients hospitalized with COVID-19 were recruited in our center at the University Hospital Heidelberg. We performed a comprehensive analysis of immune phenotype, cytokine, and chemokine profiling and leukocyte transcripts in patients with severe COVID-19 and compared critically ill patients who required mechanical ventilation and high-flow oxygen therapy and noncritically ill patient who received low-flow oxygen therapy. Results: Critically ill patients exhibited low levels of CD8 T cells and myeloid dendritic cells. We noted a pronounced CCR6 + TH17 phenotype in CD4 central memory cells and elevated circulating levels of interleukin-17 in the critical group. Gene expression of leukocytes derived from critically ill patients was characterized by an upregulation of proinflammatory cytokines and reduction of interferon (IFN)-responsive genes upon stimulation with Toll-like receptor 7/8 agonist. When correlating clinical improvement and immune kinetics, we found that CD8 T-cell subsets and myeloid dendritic cells significantly increased after disconnection from the ventilator. Conclusion: Critical illness was characterized by a TH17-mediated response and dysfunctional IFN-associated response, indicating an impaired capacity to mount antiviral responses during severe acute respiratory syndrome coronavirus 2 severe infection. Abstract : This comprehensive analysis of immune phenotype, cytokine, and chemokine profiling and leukocyte transcripts in severe COVID-19 patients suggests that immune cells might participate in the effective elimination of the virus and should be considered when developing therapeutic strategies and vaccines.